CLINICAL OUTCOMES AND AN ALGORITHM FOR SOFT-TISSUE COVERAGE AFTER ARTERIAL RECONSTRUCTION IN COMBAT-RELATED EXTREMITY VASCULAR INJURIES - Sivash, Iurii; Gumeniuk, Kostyantyn (Eastern Ukrainian Medical Journal, 2026)
Introduction. Extremity vascular injuries represent one of the most challenging forms of combat trauma due to the combination of acute limb ischemia, extensive soft-tissue destruction, and a high risk of infectious and hemorrhagic complications. Adequate soft-tissue coverage of the arterial reconstruction zone is therefore a critical factor in preventing postoperative complications. However, clear criteria for selecting the optimal reconstructive strategy remain insufficiently defined.Objective. To evaluate the clinical outcomes of different methods of soft-tissue defect closure in the area of arterial reconstruction after combat vascular trauma and to develop an algorithm for selecting the optimal coverage strategy based on defect size and the risk of postoperative complications.Methods. A retrospective analysis was performed on 85 servicemen with combat-related injuries to major extremity vessels treated at the Clinic of Vascular Surgery of the National Military Medical Clinical Center “Main Military Clinical Hospital” (Kyiv) in 2022. NPWT was used in 69 patients (81.2%) as a preparatory stage before definitive wound closure. Definitive closure techniques included primary closure, split-thickness skin grafting (STSG), flap coverage, or secondary healing. The incidence of erosive bleeding, reconstruction thrombosis, and secondary amputations was assessed, along with the timing of complications, defect size, and the number of NPWT sessions.Results. Primary closure was performed in 64 cases (75.3%), STSG in 14 (16.5%), flap coverage in 4 (4.7%), and secondary healing in 3 (3.5%). Erosive bleeding occurred in 9 patients (13.0%) with a median onset of 18 days (range 6–29 days). Two periods of increased risk were identified: days 7–10 (predominantly mechanical factors) and days 18–30 (infection-related tissue necrosis). Thrombosis of vascular reconstruction occurred in 6 patients (8.7%), all following primary closure. Secondary amputations were performed in 2 cases (2.9%). The mean defect size was approximately 15 × 20 cm in patients with erosive bleeding and 8 × 9 cm in those with thrombosis. The maximal linear dimension of the defect was used for stratification of surgical strategy. Among patients treated with NPWT, the number of sessions was higher in those who developed erosive bleeding (6–7 vs 2–3 in patients without bleeding).Conclusions. The size of the soft-tissue defect in the arterial reconstruction zone is a key determinant of postoperative complications and should guide the choice of definitive wound closure. Large defects (>15 cm) are associated with an increased risk of erosive bleeding, whereas primary closure in smaller defects may predispose to reconstruction thrombosis. Early stable vascularized soft-tissue coverage represents a pathogenetically justified preventive strategy in patients with extensive contaminated wounds. The proposed algorithm may assist in selecting the optimal reconstructive strategy in combat-related extremity vascular injuries